La incidencia de la corrupción sobre la asignación del gasto público en los países de América Latina, período 1995-2019: un análisis empírico con datos panel. - Maldonado Malacatus., Mónica Elizabeth (2022)
According to the World Bank (2020) losses due to corruption represent at least $2.6 billion dollars a year, which is equivalent to 10 times the amount of official development assistance, At the same time, Transparency International (2021) mentions that the majority of countries no progress has been made in the fight against corruption. That is why the present investigation seeks to determine the incidence of corruption in the protection of public spending in Latin American countries, period 1995-2019, for which panel data econometric techniques were used, the FMOLS model was estimated and the Granger causality test. The main results revealed the existence of a negative and statistically significant relationship in the short term between public spending and the corruption perception index, while in the long term the relationship is positive and statistically significant. Bidirectional causality between public spending and the corruption perception index globally. A policy recommendation would imply maintaining a more rigorous oversight of the activities of the central government, through a strengthened and effective judicial system.